2017
DOI: 10.1080/01900692.2017.1289390
|View full text |Cite
|
Sign up to set email alerts
|

Proud to Be a Public Servant? An Analysis of the Work-Related Determinants of Professional Pride among Dutch Public Servants

Abstract: A proud public servant is defined as someone who works honorably, conscientiously, and with dedication. Although professional pride has several positive effects on the performances of public servants, it is not instantly apparent which instruments help to stimulate pride. This study combines the Job Demands-Resources model and the High Performance Work Practices taxonomy to analyze the determinants of pride. The analysis of a large dataset of Dutch public servants shows that their professional pride can barely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 49 publications
1
10
0
Order By: Relevance
“…The Remotes and Unpaid-1 (who showed high calling scores) encompass people that principally work from home and who work to stabilize society (e.g., physicians, nurses, civil servants) [ 36 , 37 ]. Previous studies have shown that workers in these types of occupations often make sacrifices for the benefit of public motivation, and that workers in the public and health sectors (which relate to the occupations included in the Remotes and Unpaid-1 classifications) exhibit higher levels of occupational calling [ 38 , 39 ], thereby corroborating our findings. For essential workers, and especially healthcare workers, quality of life and psychological wellbeing could be affected by the stressful and traumatic events experienced in the work context [ 40 , 41 ].…”
Section: Discussionsupporting
confidence: 89%
“…The Remotes and Unpaid-1 (who showed high calling scores) encompass people that principally work from home and who work to stabilize society (e.g., physicians, nurses, civil servants) [ 36 , 37 ]. Previous studies have shown that workers in these types of occupations often make sacrifices for the benefit of public motivation, and that workers in the public and health sectors (which relate to the occupations included in the Remotes and Unpaid-1 classifications) exhibit higher levels of occupational calling [ 38 , 39 ], thereby corroborating our findings. For essential workers, and especially healthcare workers, quality of life and psychological wellbeing could be affected by the stressful and traumatic events experienced in the work context [ 40 , 41 ].…”
Section: Discussionsupporting
confidence: 89%
“…A reason might be that especially these types of semipublic employees often see their profession as a real calling (Hakanen, Bakker, & Schaufeli, 2006). In other words, semipublic personnel (i.e., educational personnel and health care personnel) might see their work as a calling to educate children/students and heal citizens (Borst & Lako, 2017) and inherently find their job intrinsically meaningful and purposeful (important aspects of work engagement). As these two groups of organizations are overrepresented in semipublic sector research related to work engagement, it could explain why work engagement is the highest among semipublic employees.…”
Section: Discussionmentioning
confidence: 99%
“…With the continuous expansion of the functions of government sectors, the workload and working content of civil servants have significantly changed. In particular, faced with the new situation of strengthening self-discipline within the Communist Party of China, severe punishment is applied for the dereliction of duty and mistakes of civil servants in recent years (18). Therefore, work tasks and job responsibilities become the major stressors of work for civil servants.…”
Section: Discussionmentioning
confidence: 99%